PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP ADOPSI SUKARELA INTERNATIONALFINANCIAL REPORTING STANDARDS DI INDONESIA - Indrawati, Novita (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
The purpose of this study was to examine the influence of the characteristics ofcompanies consisting of firm size, ownership structure, profitability, leverage,international activities and auditors reputation to voluntary adoption of InternationalFinancial Reporting Standards (IFRS) in Indonesia. The study was conducted at thecompanies listed in Indonesia Stock Exchange in 2010, as many as 345 companies.The sampling method was a purposive sampling. The collected data was analyzedusing logistic regression. The results showed that the characteristics of the companysuch as company size, ownership structure, profitability, and auditors reputation andinternational activities significantly influence the voluntary adoption of IFRS, whileleverage does not significantly influence the voluntary adoption of IFRS.Keywords: characteristics of firms, voluntary adoption, IFRS.